Bimbingan Teknis Pengembangan Lembar Kerja Peserta Didik (LKPD) Elektronik Guna Peningkatan Kompetensi Pedagogik Guru Aqidah Akhlak - Illahi, Rilci Kurnia; Khadijah, Khadijah; Gusmaneli, Gusmaneli; Masyhudi, Fauza; Azrul, Azrul (Turast: Jurnal Penelitian dan Pengabdian, 2023)
Teachers must have the ability and expertise to teach, guide and motivate students to study well. However, there are still many teachers who are unable to meet the required pedagogic competency requirements. Therefore, it is necessary to provide support to improve teacher pedagogic competence through professional training and development of E-LKPD educational technology. This helps that teacher to improve pedagogic competence. This service uses a Community Based Research (CBR) approach involving Aqidah Akhlak teachers, Madrasah Heads, MTs Supervisors in Padang City. This technical guidance is carried out in three stages, namely planning, preparation, and implementation. technical guidance activities are carried out in 2 stages, namely stage 1 regarding the description and explanation of the Basic Concepts of Teaching Materials and , Learning Objectives and Relation to Electronic Student Worksheets, Criteria for Electronic Student Worksheets. Stage 2 also conveyed the concept of electronic Student Worksheets, demonstration of making electronic Electronic Student Worksheets, and practice of making electronic Electronic Student Worksheets. Electronic Student Worksheets are technological innovations that can improve the pedagogic competence of an Aqidah Akhlak teacher. In the digital era like today, the use of technology in learning is becoming increasingly important. With the help of . Electronic Student Worksheets, teachers can create and develop learning materials online easily and efficiently. Guru harus memiliki kemampuan dan keahlian untuk mengajar, membimbing dan memotivasi peserta didik untuk belajar dengan baik. Namun, masih banyak guru yang kurang mampu memenuhi persyaratan kompetensi pedagogik yang diperlukan. Oleh karena itu, perlu diberikan dukungan untuk meningkatkan kompetensi pedagogik guru melalui pelatihan profesional dan pengembangan teknologi pendidikan E-LKPD. Hal ini membantu bahwa guru guna meningkatkan kompetensi pedagogik. Pengabdian ini menggunakan pendekatan Community Based Research (CBR) yang melibatkan guru Aqidah Akhlak, Kepala Madrasah, Pegawas MTs Kota Padang.Bimbingan teknis ini dilaksanakan dengan tiga tahapan, yaitu perencanaan, persiapan, dan pelaksanaan. kegiatan bimbingan teknis dilakukan dalam 2 tahapan yaitu tahap 1 tentang uraian dan penjelasan mengenai Konsep Dasar Bahan Ajar dan LKPD, Tujuan Pembelajaran dan Kaitannya dengan LKPD, Kriteria LKPD. Di tahap 2 ini juga disampaikan mengenai Konsep E-LKPD, Demonstrasi Pembuatan E-LKPD, dan Praktik pembuatan E-LKPD. Bimbingan teknis E-LKPD ini merupakan inovasi teknologi yang dapat meningkatkan kompetensi pedagogik seorang guru Aqidah Akhlak. Di era digital seperti saat ini, pemanfaatan teknologi dalam pembelajaran menjadi semakin penting. Dengan bantuan E- LKPD, guru dapat membuat dan mengembangkan materi pembelajaran secara online dengan mudah dan efisien